Public Policy System and Cycle in Environmental Law Changes According to Government Regulation in Lieu of Law No. 2 of 2022 - Kenuwiarja, Hendri (Green Publisher Indonesia, 2025)
A systematic process and cyclical approach are critical in formulating effective public policy, particularly in the environmental sector. This research explores the systemic and cyclical mechanisms involved in the changes to Indonesia's environmental law under Government Regulation in Lieu of Law No. 2 of 2022, which revises Law No. 32 of 2009. The objective is to assess how centralizing environmental approvals under the central government contributes to policy clarity, efficiency, and business-friendliness, while identifying potential challenges in policy dissemination and implementation across regional levels. The study uses a normative legal research method with a conceptual and statute-based approach, supported by the application of David Easton’s political system theory and Thomas Dye’s public policy cycle model. The legal documents and academic literature are analyzed using qualitative content analysis. The findings reveal that while the regulation offers procedural simplification, reduced bureaucracy, and restructured sanction mechanisms beneficial for business actors, it also poses risks of miscommunication and uneven policy implementation due to regional disparities in resources and understanding. These findings imply the need for robust socialization and capacity-building efforts to ensure uniform application. The research contributes to the academic discourse by bridging legal reform analysis with public policy system theory and recommends future empirical evaluation of regional readiness in implementing centralized environmental policies.